An Analysis of the Impact of Project-Based Learning on Students’ Creative Thinking in Islamic Education Classrooms - Rifa'i, Abdul; Munjiat, Siti Maryam (Tribakti: Jurnal Pemikiran Keislaman, 2025)
The objective of this research is to ascertain the efficacy of PjBL (Project-Based Learning) in enhancing the creative thinking skills of students in Islamic Religious Education at SMP Negeri 1 Indramayu. The present study employed a quasi-experimental methodology, whereby a control group was tested before and after the implementation of the intervention. A sample of 25 grade eight students was utilised for this purpose. The present study employed an experimental method, incorporating a group pre-test and post-test design. The subjects of this study comprised students in Year 8E, with a total of 25 students participating. The data were collected through the administration of tests, the distribution of questionnaires, and the review of documentation. The test data were analysed using paired-sample t-tests and N-Gain tests in IBM SPSS Statistics software, version 26. The findings indicate that project-based learning methodologies enhance students' creative thinking skills at SMP Negeri 1 Indramayu with considerable efficacy, as evidenced by the students' response questionnaire scores, which equated to 83.00% of the total possible score. The N-gain test revealed an enhancement in students' creative thinking skills following the implementation of a project-based learning model, with an N-gain value of 0.59 in the medium category. The implementation of project-based learning is contingent on several factors, including the role of the teacher, the availability of facilities and infrastructure, and the level of student interest in learning. Conversely, the inhibiting factors of project-based learning are the relatively high costs, the relatively long time required, and passive students. The present study indicates that curriculum designers and educators in Islamic schools should consider adopting innovative, student-centred learning models to support the development of 21^(st)-century competencies.